1975
DOI: 10.1111/j.1432-1033.1975.tb04024.x
|View full text |Cite
|
Sign up to set email alerts
|

Unspecific Arginine Kinase of Molecular Weight 150000. Amino Acid Composition, Subunit Structure and Number of Substrate Binding Sites

Abstract: The amino acid composition of unspecific arginine kinase of molecular weight 150000 of Sabella pavonina muscle has been determined. It was found to be very similar to that of the phosphagen kinases previously studied.The subunit structure of the enzyme has been investigated by physical and chemical means.The data obtained from ultracentrifugation studies in 6 M guanidine hydrochloride and from molecular sieving and disc electrophoresis in 8 M urea, as well as the tryptic peptide mapping, suggest that Sabella m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…the lobster Homarus americanus,2) the crayfish Panulirus longipes,3) the tobacco hornworm Manduca sexta,4) and the sea urchins Hemicentrotus pulcherrimus, A nth 0 cidaris crassispina, and Pseudocentrotus depressus. S ) It has been purified and characterized from various species such as the sea crayfish Jasus verreauxi,6,7) the marine polychaetous annelid Sabella pavonina, 8,9) the honeybee Apis mellijera,!O) and the squid Symplectoteuthis oualaniensis.ll) After extensive studies, it was found that argmme kinase is important in muscle contraction. Watts 12 ) has compared certain characteristics of this widespread invertebrate arginine kinase with vertebrate creatine kinase and concluded that they had a common genetic origin.…”
mentioning
confidence: 99%
“…the lobster Homarus americanus,2) the crayfish Panulirus longipes,3) the tobacco hornworm Manduca sexta,4) and the sea urchins Hemicentrotus pulcherrimus, A nth 0 cidaris crassispina, and Pseudocentrotus depressus. S ) It has been purified and characterized from various species such as the sea crayfish Jasus verreauxi,6,7) the marine polychaetous annelid Sabella pavonina, 8,9) the honeybee Apis mellijera,!O) and the squid Symplectoteuthis oualaniensis.ll) After extensive studies, it was found that argmme kinase is important in muscle contraction. Watts 12 ) has compared certain characteristics of this widespread invertebrate arginine kinase with vertebrate creatine kinase and concluded that they had a common genetic origin.…”
mentioning
confidence: 99%